Effects of Methylprednisolone on Myocardial Function and Microcirculation in Post-resuscitation: A Rat Model - Wang, Changsheng; Bischof, Evelyne; Xu, Jing; Guo, Qinyue; Zheng, Guanghui; Ge, Weiwei; Hu, Juntao; Georgescu Margarint, Elena Laura; Bradley, Jennifer L.; Peberdy, Mary Ann; Ornato, Joseph P.; Zhu, Changqing; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Previous studies have demonstrated that inflammation and impaired microcirculation are key factors in post-resuscitation syndromes. Here, we investigated whether methylprednisolone (MP) could improve myocardial function and microcirculation by suppressing the systemic inflammatory response following cardiopulmonary resuscitation (CPR) in a rat model of cardiac arrest (CA). Methods Sprague-Dawley rats were randomly assigned to (1) sham, (2) control, and (3) drug groups. Ventricular fibrillation was induced and then followed by CPR. The rats were infused with either MP or vehicle at the start of CPR. Myocardial function and microcirculation were assessed at baseline and after the restoration of spontaneous circulation. Blood samples were drawn at baseline and 60-min post-resuscitation to assess serum cytokine (TNF-α, IL-1β, and IL-6) levels. Results Myocardial function [estimated by the ejection fraction (EF), myocardial performance index (MPI), and cardiac output (CO)] improved post-ROSC in the MP group compared with those in the control group (p < 0.05). MP decreased the levels of the aforementioned pro-inflammatory cytokines and alleviated cerebral, sublingual, and intestinal microcirculation compared with the control (p < 0.05). A negative correlation emerged between the cytokine profile and microcirculatory blood flow. Conclusion MP treatment reduced post-resuscitation myocardial dysfunction, inhibited pro-inflammatory cytokines, and improved microcirculation in the initial recovery phase in a CA and resuscitation animal model. Therefore, MP could be a potential clinical target for CA patients in the early phase after CPR to alleviate myocardial dysfunction and improve prognosis.